The architecture of supervision - Miguel Ampudia; Thorsten Beck; Andreas Beyer; Jean-Edouard Colliard; Agnese Leonello; Angela Maddaloni; David Marqués Ibá\~nez (European Central Bank (ECB), 2019)
The architecture of supervision - how we define the allocation of supervisory powers to different policy institutions - can have implications for policy conduct and for the economic and financial environment in which these policies are implemented. Theoretically, an integrated structure for monetary policy and supervision brings important benefits arising from better information flow and policy coordination. Aggregate supervisory information may significantly improve the conduct of monetary policy and the effectiveness of the lender of last resort function. As long as the process towards an integrated structure does not shrink the set of available tools, monetary policy and supervision are no less effective in pursuing their objectives than a separated structure. Additionally, an integrated structure does not seem to be correlated with more price and/or financial instability, as suggested by analysing a large global set of countries with different supervisory set-ups. A centralised structure for supervision entails significant benefits in terms of fewer opportunities for supervisory arbitrage by banks and less informational asymmetry. A large central supervisor can take advantage of economies of scale and scope in supervision and gain a broader perspective on the stability of the entire banking sector, which should result in improved financial stability. Potential drawbacks of a centralised supervisory structure are the possible lack of specialisation relative to local supervisors and the increased distance between the supervisor and the supervised institutions. We discuss the implications of our findings in the euro area context and in relation to the design of the Single Supervisory Mechanism (SSM).
Keywords: E5; G21; G38; 330; Supervisory structure; central banks; lender of last resort; policy coordination